Evaluation of an HMGA2 variant for pleiotropic effects on height and metabolic traits in ponies. (21st January 2019) - Norton, Elaine M.; Avila, Felipe; Schultz, Nichol E.; Mickelson, James R.; Geor, Ray J.; McCue, Molly E.
Abstract : Background: Ponies are highly susceptible to metabolic derangements including hyperinsulinemia, insulin resistance, and adiposity. Hypothesis/Objectives: Genetic loci affecting height in ponies have pleiotropic effects on metabolic pathways and increase the susceptibility to equine metabolic syndrome (EMS). Animals: Two hundred ninety‐four Welsh ponies and 529 horses. Methods: Retrospective study of horses phenotyped for metabolic traits. Correlations between height and metabolic traits were assessed by Pearson's correlation coefficients. Complementary genome‐wide analysis methods were used to identify a region of interest (ROI) for height and metabolic traits, determine the fraction of heritability contributed by the ROI, and identify candidate genes. Results: There was an inverse relationship between height and baseline insulin (−0.26) in ponies. Genomic signature of selection and association analyses for both height and insulin identified the same 1.3 megabase region on chromosome 6 that contained a shared ancestral haplotype between these traits. The ROI contributed 40% of the heritability for height and 20% of the heritability for insulin. High‐mobility group AT‐hook 2 was identified as a candidate gene, and Sanger sequencing detected a c.83G>A (p.G28E) variant associated with height in Shetland ponies. In our cohort of ponies, the A allele had a frequency of 0.76, was strongly correlated with height (−0.75), and was low to moderately correlated with metabolic traits including: insulin (0.32), insulin after an oral sugar test (0.25), non‐esterified fatty acids (0.19), and triglyceride (0.22) concentrations. Conclusions and Clinical Importance: These data have important implications for identifying individuals at risk for EMS.